A Practical Design Method to Determine the Replacement Time of Light Embankment. (2nd August 2022) - Zhou, Fei; Yu, Fan; Xia, Tangdai; Yu, Bingqi; Hu, Yingtao
Abstract : If the settlement of bridgehead transition section of expressway is too large, it often causes frequent vehicle jumping at bridgehead and endangers passenger safety. The engineering practice has proved that the lightweight embankment replacement technology can reduce the postconstruction settlement effectively, thus reducing the occurrence of bridgehead jump. The key of filling technology of lightweight embankment is the design of filling thickness and the selection of filling time. This paper deduced how to determine the replacement time of lightweight embankment in practical engineering. In order to apply to engineering practice more conveniently, this paper made the following assumptions: (1) For normally consolidated soil, the elastoplastic deformation at any point of soil under external load can be equivalent to the sum of instantaneous elastic deformation and creep based on equivalent time. The corresponding pore ratio change also has corresponding equivalent relation. (2) The increase of equivalent time is ignored during unloading, filling, and paving process. Based on the above two assumptions, according to 1D EVP model and the conception of equivalent time, the unloading time and filling time of light embankment for layered soil foundation are deduced. It is applied to the design and calculation of the supporting project.